2005
DOI: 10.3130/jaabe.4.509
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Carbon Emission Changes in the Japanese Housing Sector from 1980-1995

Abstract: Urban development has made life convenient and comfortable. Travel has become faster, communication has become easier. However, there are externalities that we need to face due to urban development; the ratifi cation of the Kyoto Protocol and its recent enforcement has led signatory countries to limit and propose ways on how to achieve the reduction in emissions by 2012. One aspect of proposed reduction is to make urban development sustainable. Urban development is related to infrastructure systems that genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The construction process is therefore a very significant factor environmentally [5]. In addition, the CO 2 emission factor is very important in the construction industry [6], and the amount of energy and number of materials consumed during the construction process is considerable [7]. During the life cycle of a building, a large amount of CO 2 is also generated in the operation process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The construction process is therefore a very significant factor environmentally [5]. In addition, the CO 2 emission factor is very important in the construction industry [6], and the amount of energy and number of materials consumed during the construction process is considerable [7]. During the life cycle of a building, a large amount of CO 2 is also generated in the operation process.…”
Section: Introductionmentioning
confidence: 99%
“…In the study of the material production phase, the Korea Life Cycle Inventory Database (LCI DB) was used to determine CO 2 emissions for each task, and the actual amount of oil consumption for (1) Civil engineering works: soil cement wall (SCW) work, pre-stressed high-strength concrete (PHC) pile work, earthwork, appurtenant work; (2) Reinforced concrete works: rebar, formwork, concrete construction, lifting, and temporary work; (3) Steel-frame works: steel structure erection, deck plate; (4) Metal and window work; (5) Glass work; (6) Interior finishing works: masonry/plaster work, waterproof work, painting/insulation work; (7) Exterior finishing work; (8) Ground heat construction: closed/open loop.…”
Section: Introductionmentioning
confidence: 99%
“…( 1)), the structural effect (a change in L ), and the final-demand effect (a change in f ). Yabe (2004) decomposed changes in CO 2 emissions in Japan between 1985 and 1995 and found that both the carbon-intensity and structural effects contributed to an emission reduction during the late 1980 s but not during the recession in the early 1990 s. Gerilla et al (2005) similarly decomposed a change in carbon emissions in the Japanese housing sector during 1980-1995 and revealed the contributions from each effect. Okamoto (2013) further segregated each effect into four segments of the economy and concluded that contributions of the transitions to a service economy were not negligible during 1990-2005.…”
Section: Overview Of Methodologiesmentioning
confidence: 99%